Vγ9Vδ2 T-cell immunotherapy in blood cancers: ready for prime time? - Giannotta, Claudia; Autino, Federica; Massaia, Massimo (Frontiers in Immunology, 2023)
In the last years, the tumor microenvironment (TME) has emerged as a promising target for therapeutic interventions in cancer. Cancer cells are highly dependent on the TME to growth and evade the immune system. Three major cell subpopulations are facing each other in the TME: cancer cells, immune suppressor cells, and immune effector cells. These interactions are influenced by the tumor stroma which is composed of extracellular matrix, bystander cells, cytokines, and soluble factors. The TME can be very different depending on the tissue where cancer arises as in solid tumors vs blood cancers. Several studies have shown correlations between the clinical outcome and specific patterns of TME immune cell infiltration. In the recent years, a growing body of evidence suggests that unconventional T cells like natural killer T (NKT) cells, mucosal-associated invariant T (MAIT) cells, and γδ T cells are key players in the protumor or antitumor TME commitment in solid tumors and blood cancers. In this review, we will focus on γδ T cells, especially Vγ9Vδ2 T cells, to discuss their peculiarities, pros, and cons as potential targets of therapeutic interventions in blood cancers.